To Assess the Knowledge and Extent of Compliance Regarding the Prevention of Foot Ulcers among the Patients with Diabetes Mellitus at Selected Settings in Chennai - Muthurajathi Muthuramu (Innovational: Journal of Nursing and Healthcare, 2025)
Background: Diabetic foot ulcers (DFU) are a serious complication of diabetes that can lead to infections, hospital stays, and even amputations. Preventing these ulcers largely depends on how much patients know and how well they follow self-care practices. This study was carried out in selected outpatient departments of diabetic care centers in Chennai. The main goals were to assess patients’ knowledge and compliance, see if there is a link between the two, and find out if factors such as age or education influence them. Methods: A non-experimental descriptive study was conducted among 60 diabetic patients attending outpatient departments in selected health-care settings in Chennai. A non-probability convenience sampling technique was used. Data were collected using a semi-structured interview schedule consisting of demographic variables and questionnaires to assess knowledge and compliance regarding the prevention of DFU. Descriptive and inferential statistics were applied to analyze the data. Results: Among the participants, 48.33% had moderate knowledge, 35% had inadequate knowledge, and only 16.67% had adequate knowledge regarding foot ulcer prevention. In terms of compliance, 51.67% exhibited moderate compliance with preventive measures, 43.33% had low compliance, and just 5% showed high compliance. A statistically significant positive correlation was found between knowledge and compliance (r = 0.674, P < 0.001), indicating that better knowledge was associated with better compliance. Conclusion: The study concludes that diabetic patients’ knowledge and compliance with preventive measures are key to reducing foot ulcer risk. Moderate levels observed highlight the need for structured education and ongoing support to improve self-care and diabetes outcomes.